Secondary metabolites in in vitro cultures of Ginkgo biloba L. - Szewczyk, Agnieszka (2007)
Ginkgo biloba callus cultures were established from male and female leaves explants. Suspension cultures were derived from callus cultures. Murashige-Skoog medium supplemented with Picloram (4 mg/l) and BAP (2 mg/l) was the best medium for further in vitro cultures cultivation. The contents of ginkgotoxin and pyridoxamine were analysed in leaves, seeds and in vitro cultures. The comparison of ginkgotoxin and pyridoxamine contents in male and female leaves collected every week in July 2005 revealed that in the middle of July the amount of ginkgotoxin is the highest.The contents of monomeric flavonoids and phenolic acids after hydrolysis of glycosides and biflavonoids were investigated by HPLC method. The results suggest that G. biloba in vitro cultures can accumulate these compounds, but only in small amounts. The phytochemical analysis of methanol extracts from callus cultures (two lines) resulted in the isolation of 12 compounds which were identified as β-sitosterol, 7-oxo-β-sitosterol, 7α-hydroxy- and 7β-hydroxy-β-sitosterol, 3-O-β-glucopyranoside-β-sitosterol, p-hydroxycinnamic alkohol, esculetin, ethyl p-hydroxybenzoate, p-hydroxybenzoic acid, caffeic acid, protocatechuic acid, 6-hydroxykynurenic acid. The occurence of these compounds in in vitro cultures of the plant was been shown for the first time.
Keywords: in vitro cultures; Ginkgo biloba; secondary metabolites

Search for selective A1 and A2A adenosine receptor ligands - Yuzlenko, Olga (2008)
Keywords: xanthine derivatives; A1 and A2A adenosine receptors; 3D-QSAR; molecular modelling; docking

The effects of primary coronary angioplasty techniques and adjunctive pharmacotherapy on left ventricular function and myocardial perfusion - Zorkun, Cafer Sadik (2006)
Keywords: acute myocardial infraction; primary PCI; facilitated PCI; ST segment resolution; STEMI; myocardial perfusion grade; TIMI frame counts; adjunctive pharmacotherapy

Influence of some aroxy-ethyl-amins derivatives on antioxidant system in the human blood and the human placenta - Pietrzycka, Agata (2003)
The aim of the study was to investigate aroxyethylamins derivatives influence on antioxidant system of the human blood, human placenta and fetal membranes. Ferric reducing ability of plasma (FRAP), superoxide dismutase (SOD) and catalase (CT) activities in red blood cells and placental homogenates were determined. Antioxidant properties of studying compounds were compared to well known antioxidants: Trolox, Resveratrol and -Carotene. Overall results strongly suggest that: 1/ FRAP values in he blood samples increased more after incubation with -Carotene than with Trolox or Resveratrol; 2/ -Carotene and Trolox increased CT activity whereas Resveratrol increased SOD activity. 3/ 4-orto-methoxyphenylpiperazine derivatives had antioxidant properties. 1 substituent at the phenoxyl group predisposed compounds toinfluence on CT and FRAP. 2 substituent at the same chemical group led to impact of SOD activity. 4/ Derivatives with xanthone structure and amin-butanol groups characterized prooxidative properties. These compounds decreased antioxidant enzymes activities.
Keywords: FRAP; SOD; CT; aroxylethylamins derivatives

The relationship between social, economic, environmental and demographic characteristics, resources and activities of health care and mortality. Ecological analysis of the Polish 66 subregions - Genowska, Agnieszka. (2011)
The aim of this study was to assess the relationships between population health and its socio-economic and demographic position, environmental pollution and resources and activities of health care. Ecological study was performed, in which the statistical information available for the Polish population of 66 subregions for the years 2006-2008 was used. For the analysis 26 variables were used describing demographics, socio – economic conditions, environmental pollution, natural resources and health care actions, and 8 factors describing health status. Results for repeated measurements were statistically analyzed based on a statistical model of Generalized Estimating Equations GEE, to take account of variables and related relationships between variables. Statistical analysis was performed using R programme version 2.11.1 using the package „gee” version 4.13. Among demographic characteristics, adverse health effects were related to the ratio of divorces. Better socio - economic position, the existence of numerous non-governmental organizations and human resources in health care were associated with lower mortality and longer life expectancies, and better housing conditions were associated with lower infant mortality. Worse working conditions were associated with the shortening of life for women and higher infant mortality. Health inequalities between the 66 sub-regions can be partly explained by the Polish differentiation of socio - economic characteristics.
Keywords: health determinants; health inequalities; ecological study

The evaluation of the effectiveness of inguinal hernia repair usingvarious tension-free techniques (Lichtenstein, Rutkow-Robbins, andPHS) in the analyzed group of patients operated on between 1999-2009 at the Ist Chair of General and Gastrointestinal Surgery,Jagiellonian University Medical College - Kamtoh Tebug, Georges. (2011)
ObjectivesThe aim of the dissertation was to compare treatment resultsfrom the patients operated for inguinal hernias with Lichtenstein,Rutkow-Robbins, and PHS techniques. The other endpoint was theanalysis of the associations between:· the technique and the frequency of early complications, such aswound suppuration, hematoma in the wound, seroma, edemaof scrotum, pudendal lip or of testicles, spermatic cord cyst,testicle atrophy, and the frequency of late complications, i.e.hernia recurrence,· hernia recurrence and timing of surgery, duration of hospitalstay, and electiveor emergency surgery,· frequency of complications and type of hernia acc. to the Nyhusclassification,· postoperative pain duration (>3mo., chronic pain) and painintensity (scored by the10-point VAS scale),· pain intensity, age and body mass (BMI) of the patients,· BMI and frequency of recurrences (average BMI among thepatients with and without hernia recurrence),· hernia repair technique and problems with assuming dailyactivities,· sexual functions and hernia repair technique,· timing of surgery and individual hernia repair techniques.
Keywords: inguinal hernia; tension-free techniques; chronic pain

Studies on the accumulation of selected groups of biologically active secondary metabolites in Schisandra chinensis (Turcz.) Baill. in vitro cultures - Szopa, Agnieszka (2013)
Schisandra chinensis - Chinese magnolia vine (Schisandraceae) is a dioecious vine native to some regions of Southeastern Asia. It is a new pharmacopoeial species in the European medicine from 2008 and also in Polish medicine (from 2009). Schisandra fruits are a rich source of lignans, dibenzocyclooctadiene derivatives. These compounds are highly valued mostly for their adaptogenic, hepatoprotective, antioxidant and anticancer properties.This work aimed to establish Schisandra chinensis in vitro cultures and to analyze two groups of therapeutically important compounds: lignans and phenolic acids. The further goal of these studies was to propose in vitro cultures as a potential source of the abovementioned groups of compounds.In vitro cultures with different degree of differentiation (shoot-differentiating callus cultures and undifferentiating callus cultures) were successfully established from leaf buds of female Schisandra plants. At the next stage of research, culture conditions were optimized by testing several variants of the Murashige and Skoog (MS) medium differing in the contents of plant growth regulators: the cytokinin BAP (6-benzyloaminopurine) and the auxin NAA (α-naphthaleneacetic acid), in the concentration range from 0.1 to 3.0 mg/l, and by examination of different types of in vitro cultures: agar (shoot-differentiating callus and callus) cultures and agitating (shoot and suspension) cultures. The next stage of research involved HPLC determination of the composition and contents of four main lignans of Chinese magnolia vine and eleven phenolic acids, cinnamic and benzoic acid derivatives and the parent compound of one of the subgroups of these compounds - cinnamic acid. Free phenolic acids - FPA and total phenolic acids – TPA, free and bound phenolic acids (obtained after acid hydrolysis), were estimated.The established shoot-differentiating callus cultures were characterized by a distinct capability of deoxyschisandrin production. The contents of schisandrin and gomisin A were also high while γ-schisandrin amounts were lower. The studies demonstrated the effect of plant growth regulators on the lignan production. In addition, it was shown that the cultures at the higher level of differentiation produced many times greater amounts of these compounds than undifferentiating callus cultures.The maximum contents of lignans equaling 308.51 mg/100 g d.w. for deoxyschisandrin, 86.41 mg/100 g d.w. for gomisin A, 75.54 mg/100 g d.w. for schisandrin and 22.09 mg/100 g d.w. for γ--schisandrin, were obtained in agar shoot-differentiating callus.
Keywords: Schisandra chinensis; in vitro cultures; Schisandra chinensis lignans; phenolic acids; plant growth regulators

The influence of opioids on the humoral and cell-mediated immune responses in mice - Filipczak-Bryniarska, Iwona. (2013)
Background: Experiments were aimed to test the influence of treatment with different opioids (morphine, fentanyl, methadone) on the humoral and cell-mediated immune responses. Methods: Mice were treated intraperitoneally with opioids and either immunized with sheep red blood cells (SRBC) to test the antibody production or skin-sensitized with hapten picryl chloride to induce contact hypersensitivity. The effects of opioids on the production of reactive oxygen intermediates and cytokines by peritoneal macrophages and on the expression of surface markers on these cells and blood leukocytes were estimated. Results: Opioids caused an enhancement of reactive oxygen intermediates and cytokines production when macrophages were stimulated with zymosan or LPS and reduced the expression of antigen presentation markers on macrophages. Numbers of anti-SRBC plaque forming cells and antibodies titres were lower in mice treated with all tested opioids. Effects of the opioid treatment on contact hypersensitivity were diverse. While morphine decreased the early and late phases of induction of contact hypersensitivity responses, methadone increased both reactions. In case of the effector phase of contact hypersensitivity response, morphine and fentanyl increased both its early and late stages, while methadone decreased the late reaction. Conclusions: The results of experiments show in disertation that the action of opioids on the immune system depends on type of opioid, character of response (humoral versus cellular) and types of cells involved. Here macrophages seem to play a significant role.
Keywords: opioids; macrophages; immunity; immunosuppression

Diabetic Charcot foot - a risk of development and the estimation of effectiveness of the treatment model - Friedlein, Jacek. (2012)
Charcot neuroarthropathy is a condition affecting mainly the foot and progressing with bone destruction and an inflammatory process of soft tissues of the foot.The Charcot foot occurs in patients with advanced neuropathy. The etiopathogenesis of the Charcot foot has not been fully explained. To this day, Mitchell and Charcot’s theory and Volkman’s theory have been widely used. Nowadays there are more and more followers of the new theory of bone turnover disorders in Charcot joint, dysregulated OPG/RANKL/RANK axis - the axis that is involved in regulating bone turnover.The aim of the study was to describe patients who are at high risk of developing Charcot joints by determining causative factors and the progression of radiological changes. Also to establish the possibilities of secondary preventive procedures to avoid the Charcot foot. Finally, to evaluate healing after skin grafting and to introduce optimal treatment methods of Charcot joints.Material and methods: The subject of the study were patients treated at the outpatient clinic of the Orthopedics Department CMUJ and the outpatient clinic of the II Chair of Surgery CMUJ between 1995 and 2009. The final analysis included 60 subjects in the 22 - 74 age bracket. In this group, 22 patients with type 1 diabetes, and 38 patients with type 2 diabetes. The shortest observation period for patients was over 12 months. A number of examinations were performed in order to confirm the diagnosis of polyneuropathy: sensation of pressure examination, sensation of pain examination, temperature sensitivity test and vibration perception test. Tendon reflexes were also examined. In all patients radiological and pedobarographic examinations as well as densitometry tests were performed. Conclusions: Charcot joints occur more frequently in type 2 diabetic patients with unsatisfactory blood glucose control and after many years of having the disease. Changes are one-sided and ulcers rarely form at the onset of the disease. Treatment, according to clinical practice recommendations, in 100% convert active process to non-active.
Keywords: diabetes; neurophaty; Charcot foot

Long-term clinical evaluation, ECG, and the quality of life of patients treated with pacemaker implantation - Kostkiewicz, Marcin. (2013)
Introduction There has been increasing interest in HRQoL among clinicists. HRQoL has been also studied in patients treated with pacemaker (PM) implantation.However, there are no comprehensive analyses addressing relationships between HRQoL and factors which are not directly related to electrode localization or pacemaker mode.The aim of the work was5. To determine clinical characteristics of patients undergoing PM implantation.6. To analyze changes of these parameters in 1.5-year follow-up.7. To analyze HRQoL in patients after PM implantation.8. To identify factors influencing HRQoL and its change after PM implantation.Materials and methodsThe study was performed in a group of 101 adults who received PM due to SSS and/or AVB.The study population was assessed prospectively. Two questionnaires were completed on study start and end of follow-up period: first one, prepared by the author, and second one – NHP questionnaire to assess HRQoL.Results and conclusionsBased on analyses performed, the following conclusions can be made:5. Significant increase in HRQoL occurs after PM implantation.6. PM recipients have usually many comorbidities and adverse lifestyle that does not change after PM implantation. These factors affect HRQoL.7. Indications for PM and pacing mode do not explain fully the HRQoL changes occurring after implantation.8. Post-implantation HRQoL change is largely determined by sociodemographic factors, such as: sex, place of residence, education and social support and care.
Keywords: QoL; pacemaker; ECG; clinical characteristics

Day reconstruction in older individuals in relations to functional status, chronic health conditions and structure of the household - Zawisza, Katarzyna. (2013)
The Day Reconstruction Method (DRM) is an instrument to measure subjective well-being in large population surveys based on affective rating of experiences connected with time-budget data.The aim of the study was to assess validity and reliability of the DRM among Polish older population as well as to provide information about time budged of older people and to find some determinants of time budged and subjective well-being people aged 65 and over.Data for this investigation were obtained from the COURAGE project. The analysis was performed on a random sample of 1992 non-institutionalized older people from Poland. The interviews were conducted using structured questionnaire which include an abbreviation version of the DRM, the WHODAS II to assess functional health status, questions about self-rated health, presence of chronic diseases and household structure.The DRM showed good internal consistency and convergentvalidity.The analysis showed that older people spent around 67% of their awakening time in solitude. Spending most of time alone decreased well-being of respondents. Moreover, older people allocated most of their time on physical inactivity, what was related with worse health and functional status. Better functional status was associated with higher level of well-being. Significant association between well-being and time spent on physical inactivity among older individuals with very poor self-rated health was shown. More time spent on doing housework or shopping was associated with better functional status but pending most of time on daily living activities was related to worsening of well-being.
Keywords: The Day Reconstruction Method; time budget; subjective well-being; older people

Pharmacotherapy of diseases from the spectrum of eczema – an analysis of the concordance between recent expert guidelines, official drug licenses, and evidence for efficacy of recommended drugs - Kordus, Katarzyna. (2013)
Physician's and Dentist's Profession Act (PDPA) imposes an obligation on Polish physicians to prescribe only drugs licensed for trade in the Republic of Poland. The Office for Registration of Medicinal Products, Medical Devices and Biocidal Products authorizes the introduction of drugs to Polish market based upon the Summary of Product Characteristic (SPC) that - among others - defines the official indications for the use of a drug. According to the Polish Act on Pharmaceutical Law and the PDPA, prescribing a drug for treating diseases that are not among official indications listed in the SPC ('off-label' use) could be interpreted as a ‘medical experiment’, leading to a range of legal and financial consequences for the doctor. Moreover, the ‘off-label’ prescription results as a rule in the denial of drug reimbursement. The aim of this study was to analyze the concordance between official indications as determined in the SPC of drugs registered in Poland for treating diseases from the spectrum of eczema with up-to-date expert guidelines and the scientific evidence for the efficacy of recommended and registered of recommended and registered drugs. The policy of drug reimbursement was also analysed with this regard.
Keywords: eczema; pharmacotherapy; expert guidelines; Summary of Product Characteristics; “off-label” drug prescription

Investigation of mechanisms of the anti-atherosclerotic effect of agmatine in apoE knockout mice - Wiśniewska, Anna (2012)
Agmatine is an endogenous polyamine produced by decarboxylation of L-arginine and exerts a wide array of biologic effects. It has been shown that agmatine has anti-inflammatory function, inhibits the proliferation of smooth muscle cells, protects the mitochondria and modulates fatty acid metabolism. These properties of agmatine makes it an interesting candidate for anti-atherosclerotic compound. The aim of the study was to investigate the effect of exogenous agmatine on the development of atherosclerosis in apoE-knockout mice and identify the most probable mechanism responsible for anti-atherosclerotic action of agmatine.The research was carried out on male apoE-knockout mice at the age of 8 weeks. Animals was divided into two groups: control group (on chow diet, n=10) and treatment group (on chow diet mixed with agmatine, dose 20 mg per kg of body weight per day, n=8). Both methods en face and cross section showed that agmatine by 40% inhibited formation of atherosclerotic plaques. Immunohistochemistry showed that agmatine may increase plaque stability by decreasing number of macrophages. What’s more, action of agmatine was associated with increase of the high density lipoproteins (HDL) in blood. Real-Time PCR analysis showed that modulates the oxidation of fatty acid and cholesterol biosynthesis. Widespread mitochondrial action of this drug has been demonstrated by proteomic methods as well.We are tempted to speculate that in the future, compounds with similar mechanism of action could represent new group of drugs for prevention and/or treatment of atherosclerosis and coronary heart disease.
Keywords: atherosclerosis; agmatine; apoE-knockout mice; mitochondria; lipid metabolism

Immunomodulating properties of bacterial cell wall components derivedfrom Lactobacillus. Role of exopolysaccharide - Ciszek-Lenda, Marta. (2012)
The aim of this work was to compare immunomodulating properties of exopolysaccharide (EPS) isolated from L. rhamnosus KL37C with properties of pure exopolysacharide (EPS37), lipoteichoic acid (LTA) and LPS from E.coli. Data shows that, EPS stimulated murine macrophages to secrete inflammatory mediators, but to less extent than the full bacteria L.rhamnosus. The potency of EPS was weaker than that of the LPS, but the cytokine release profile was similar, which indicates a proinflammatory potential of the EPS. Activation of cytokine synthesis by the EPS, LPS and the LTA required activation of the same MAP kinases. In vivo, EPS inhibited the humoral immune response against ovalbumin (OVA) and abolished the adjuvant effect of the LPS. Pure EPS37 did not stimulate cytokine production by macrophages. In oposition to the LTA, the EPS37 did not induce synthesis of the PGE2 by macrophages, nor did it affect expression of the COX-2 protein in cells. EPS37 had no effect on phagocytosis of dextran molecules by macrophage cells. Both the EPS37 and the LTA decreased ROS production in the neutrophils stimulated with zymosan. The tested factors induced production of the IL-12p40 and very low levels of the IL-6 in DC. However stimulation with EPS37 did not lead to the synthesis of IL-10. EPS37 and LTA had an effect on antigen presentation and processing, showed by the activation of OVA-specific lymphocytes measured by an increase in the synthesis of the IL-2. BothEPS37 and LTA, like EPS, inhibited the OVA-specific humoral immune response and abolished the LPS adjuvant effect.
Keywords: exopolysaccharides; Lactobacillus rhamnosus; probiotics; cytokines; macrophages

Chemokine RANTES level and it’s association with endothelial dysfunction in patients with diabetes, high cardiovascular risk and cardiovascular disease - Podolec, Jakub. (2012)
ObjectivesTo estimate levels of chemokine RANTES and it’s association with endothelial dysfunction in two different groups of patients: with diabetes at high cardiovascular risk and stable angina undergoing coronaroangiography.MethodologyGroup I: level of chemokine RANTES in serum was assessed in 128 consecutive patients at the average age of 56,6 (from 43 to 72 y.o.; SEM=0,56) with diabetes. Brachial flow mediated dilation (FMD) and vWillebrandt factor (vWF) were used to asses endothelial dysfunction. Measurement of Intima-media thickness (IMT) in carotid arteries was assesed to evaluate patients with and without atherosclerotic plaques. MDA levels were measured to analize RANTES association with oxydative stress. Group II: level of chemokine RANTES in serum was assessed in 62 consecutive patients at the average age of 59,3 (from 46 to 78 y.o.; SEM=0,94) with stable angina pectoris undergoing coronarography. Number of diseased coronary arteries was analized. More than 50% stenosis was considered as hemodynamically significant. Three or more arteries significantly narrowed were considered as multivessel disease. Patients were qualified to two subgroups (multivessel disease vs. less severe atherosclerosis ≤2 significantly stenosed arteries). Risk factors of coronary artery disease and inflamatory marker IL-18 were analyzed in all patients. Levels of chemokine RANTES were measured in both groups by ELISA method and expressed in ng/ml. ResultsAnalysis of risk factors of CAD showed no significant correlations in both groups of patients except of cholesterol level in group I. Significant correlations between RANTES level and endothelial dysfunction measurements (FMD (r=0.018, p<0.05) and vWF (r=0.007, p<0.01)) have been found. Results showed inverse correlation between RANTES level and in IMT assesment (r=0.012, p<0.05). MDA as marker of the oxydative stress and RANTES level showed also inverse correlation (r=0.033, p<0.05). Inverse correlation have been found between RANTES level and IL-18 (p<0.05). In group II significant correlations have been found between chemokine RANTES level and number of diseased coronary arteries (p<0.03). ConclusionsChemokine RANTES level measured in serum is a significant early marker of endothelial dysfunction. Inverse correlations between chemokine RANTES level, IMT and MDA measurements may indicate late distribution of RANTES from peripheral blood to endothelial cells in patients with later stages of atherosclerosis. Elevated RANTES level may evaluate patients to high risk group with endothelial dysfunction. Chemokine RANTES level is a significant marker of severity of coronary disease. RANTES is an early marker of inflammation, but it’s level is lower in patients with diffuse atherosclerosis. High level of chemokine RANTES in patients with stable angina pectoris may evaluate patients to high risk group.
Keywords: RANTES; IL-18; diabetes type 2; stable angina

Contribution of microvesicles in pathomechanism of diabetic retinopathy - the study of selected factors involved in angiogenesis - Tokarz, Aleksandra (2018)
Diabetes and its complications still cause very serious health problems having social and economic impact on society. The classification of diabetes complications distinguishes two types of them: macroangiopathies and microangiopathies. Retinopathy is the most prevalent one among microangiopathies; it is the main cause of sight loss in patients who are professionally active.This study is dedicated to the evaluation of factors, potentially significant from the pathophysiological perspective, such as extracellular vesicles (EV), selected factors involved in angiogenesis namely angiopoietin-2 (Ang-2) and chemokine RANTES (RANTES), along with their receptors transferred by annexin V-positive microvesicles (MVAnnV+). The aim of this study was characteristic the number and profile of EV among diabetic patients in compare to a control group. The grade and severity of diabetic retinopathy, as well as the efficient diabetes managing were taken into consideration during analysis.The study extends the knowledge about extracellular vesicles in patients with diabetes and the expression of receptors Tie-2 and CCR5 on the surface of microvesicles presented in plasma. There is a need for further research to assess the pathophysiological role of MV and RANTES in retinopathy progression, including the effect of statins and acetylsalicylic acid therapy. Results reveal the contribution of microvesicles as new conveyors in vascular diabetic complications and may be used to propose the new model of angiogenesis in diseases progression.
Keywords: microvesicles; diabetes; retinopathy; RANTES; angiopoietin-2

Assessment of the effect of vesicourethral anastomosis using single-knot running suture according to own study and van Velthoven single running suture for the effectiveness of restoration of urinary tract continuity, occurrence of postoperative complications and quality of life of patients with prostate cancer and subjected to laparoscopic radical prostatectomy - Dudek, Przemysław (2018)
Aim The aim of this experiment was to investigate the surgical efficiency (including procedure time, drainage time and hospital stay), complications profile (including bladder neck stenosis and urinary incontinence) and patients' quality of life after the surgery as a result of a single absorbable running suture (Van Velthoven variant) versus single-knot running suture (Chlosta variant) for vesico-urethral anastomosis during laparoscopic radical prostatectomy.Materials and methods Totally, 82 consecutive patients were prospectively included in the study. The inclusion criteria applied to the study recruitment were: patient’s age ≤ 70, biopsy proven prostate cancer, organ-confined disease, PSA ≤ 20 ng/ml, pathological grade defined by the Gleason score ≤ 7, two-lobe prostate without the middle lobe.Patients were classified into two groups: I- with vesico-urethral anastomosis using the single-knot running suture technique (Chlosta variant) and II - the single running suture technique (Van Velthoven variant). The study analyzed vesico-urethral anastomosis time, operative time, drainage time, blood loss and anastomotic leak assessed by creatinine concentration in drainage output.Lower urinary tract symptoms and patients’ quality of life were investigated with IPSS and QoL questionnaires 6 months after the procedure. Urinary continence status was assessed with the pad test at 3, 6 and 12 months. Urine flow (uroflowmetry) and possible urethral strictures were evaluated at 6 and 12 months. Results The two analyzed groups were comparable in terms of descriptive statistics, clinical stage, pathological grade, preoperative prostate-specific antigen and prostate volume. There were no significant differences between groups in blood loss, drainage time and catheterization time. The total peri-operative and long-term complication rates were similar as well. The pathological T stage and Gleason scores were not statistically different between the 2 groups. However, the mean anastomosis time and the total operative time were significantly shorter for patients who underwent the single-knot running suture technique (p<0,001, p=0,02, respectively). Furthermore, the mean urine flow and the maximal urine flow were statistically higher in this group of patients (p=0,05, p=0,01, respectively). Conclusion The single-knot running suture technique is a safe method of vesico-urethral anastomosis for laparoscopic radical prostatectomy with complications profile comparable to the single running suture technique. Nonetheless, the mean anastomosis time of the single-knot running suture technique is shorter than that of the Van Velthoven technique and it leads to better urine flow observed during follow up.
Keywords: prostate; cancer; prostatectomy; vesicourethral anastomosis

Pharmaceutical profile evaluation of selected selenoorganic compounds and hydantoin derivatives with potential application in the therapy of cancer - Marć, Małgorzata Anna (2018)
The search for new anticancer drugs and adjuvants in cancer therapy is an important challenge of the pharmaceutical sciences. The aim of this study was the biological, pharmacological, pharmaceutical and safety profile evaluation of 25 selected active representatives of organic selenocompounds and hydantoin derivatives. In order to complete the biological activity screening, the cytotoxic activity evaluation on the neuroblastoma and astrocytoma central nervous system derived cell lines was conducted. Furthermore, the determination of the anti/pro-oxidant activity and drug combinational assays with doxorubicin were performed. In addition, the safety and pharmacological profiles of the tested derivatives were also estimated.The results of the experiments proved that either tested organic selenocompounds or hydantoin derivatives can become potential candidates for anticancer drugs or adjuvants in anticancer therapy. Especially, selenoesters, due to their strong antitumour activity, may also become drug candidates for modern chemotherapeutic compounds, which can act synergistically with commonly used anticancer agents. The most active selenocompounds turned out to be ketone-containing selenoesters (EDA-71, EDA-73), or methyl selenoesters with a pyridine ring and two selenium atoms (EDA-119) as well as a cyclic phthalic selenoanhydride (EDA-A6). Among hydantoins the best pharmaceutical profile achieved arylpiperazine hydantoin derivatives with diaromatic moiety at position 5, i.e. the (spiro)fluorene compounds (AR-3, AR-5) and 5,5-diphenylhydantoin derivative ML-2.
Keywords: selenocompounds; hydantoin derivatives; cancer

Evaluation of selected proinflammatory cytokines in psoriatic and psoriatic arthritis patients with coexisting metabolic syndrome - Pirowska, Magdalena (2018)
INTRODUCTION: Psoriasis is a common chronic skin disease. In recent years,research has shown the association of dermatosis with numerous accompanyingdiseases, most often with cardiovascular diseases and metabolic syndrome,determining psoriasis as a predisposing factor.OBJECTIVE: The aim of this dissertation was to evaluate the epidemiology ofpatients with psoriasis and psoriatic arthritis and to study the levels of TNF-α, IL-12,IL-23 and IL-17 in patients’ blood in correlation with individual components of themetabolic syndrome.MATERIAL AND METHODS: A retrospective study evaluated data from 3,331hospitalizations and 1,537 outpatient cards of patients with psoriasis. For the studyof cytokines 60 patients with severe psoriasis were included. Control groups were:15 subjects diagnosed with metabolic syndrome and 15 healthy voluntary subjects.The concentrations of IL-12, IL-17, IL-23 and TNF-α in serum were determined.RESULTS: The level of the studied cytokines: IL-23 and TNF-α was higher inpatients diagnosed with psoriasis in comparison to the control group. Higher levelsof IL-17 were observed in patients with metabolic syndrome associated withpsoriasis. The level of cytokines was also assessed in relation to the presence ofspecific co-morbidities that are components of the metabolic syndrome. The level ofIL-17 was higher in the group of patients diagnosed with diabetes mellitus anddislipidemia. In the study, a higher level of IL-17 and IL-23 was also shown, inpatients with psoriatic arthritis in comparison to patients with normal psoriasis.CONCLUSIONS: It seems very important to study immunologic mechanismsresponsible for the presence of psoriasis to personalize the therapy and optimize theeffect of action on the basic disease and on concomitant disorders.*
Keywords: psoriasis; psoriatic arthritis; metabolic syndrome; proinflamatorycytokines

The influence of specific metabolic and hormonal disorders on the type of symptoms and the presence of complications in gastroesophageal reflux disease - Krakowska-Stasiak, Małgorzata (2019)
Introduction: The aim of the study is to evaluate the differences in course of gastroesophageal reflux disease (GERD) depends on co-existing obesity, diabetes and thyroid diseases.Material and methods: 258 patients with GERD were included. In the first stage of the study, the impact of BMI (body-mass index) on the course of GERD was analyzed. Then, the symptoms and gastroscopy results were compared depending on the coexistence of diabetes. The third stage involved patients with GERD and concomitant thyroid diseases. Correlations between anthropometric and biochemical parameters and severity of reflux symptoms and endoscopic image were assessed.Results and conclusions: (1) The results present differences in the clinical course and endoscopic changes in GERD depending on coexisting obesity, diabetes and thyroid diseases. (2) Overweight predispose to esophageal inflammation and increase the frequency of heartburn and sleep problems in GERD patients. (3) Patients with diabetes and GERD are more likely to complain of post-prandial heartburn and have a higher percentage of inflammatory changes in the esophagus. (4) Patients with GERD and thyroid diseases complained more often of burning in the throat and less commonly presented with inflammatory changes in the esophagus. (5) Overweight and obesity in patients with a thyroid disease are not the principal risk factors favoring the development of reflux symptoms.
Keywords: gastroesophageal reflux disease; obesity; overweight; diabetes mellitus; thyroid diseases

Effect of calorie restriction on the development of atherosclerotic - molecular mechanisms - Kostogrys, Renata B. (2019)
Calorie restriction (CR) is a dietary intervention that contributes to extending the life of mammals. Limiting caloric intake affects blood lipid profile parameters, thus delaying the occurrence of many diseases associated with energy disorders. The effect of calorie restriction may vary depending on the age of the model animals. The aim of the study was to determine the effect of calorie restriction on the development of atherosclerosis in young and old ApoE/LDLR-/- mice. Two feeding models AIN-93 control diet and atherogenic Western diet were studied. To confirm the effect of CR by activation of the FMO3 gene, mice were fed diet supplemented with choline (0.5% and 1%). It was shown that calorie restriction reduced body weight in old and young animals fed AIN-93 and Western diets. Calorie restriction significantly increased total cholesterol and LDL cholesterol, as well as reduced HDL cholesterol in young mice in both dietary models. Additionally, calorie restriction significantly reduced the concentration of triacylglycerols in young and old animals fed a control diet. This effect was not observed in animals fed a Western diet. Saturated fatty acids in adipose tissue were significantly increased but unsaturated fatty acids were decreased in young mice. Regardless of the diet, dietary restrictions reduced the area of atherosclerosis in old mice, whereas CR increased atherosclerosis in the entire aorta in young mice. FMO gene expression was increased in young mice, which indicated effect CR on intestinal microbiota. It was observed that choline in the diet (0,5% and 1%) significantly increased the area of atherosclerosis in ApoE/LDLR-/- mice. Caloric restriction applied to old and young ApoE/LDLR-/- mice fed control and atherogenic diets showed a different, opposite effects on the development of atherosclerosis.
Keywords: calorie restriction; atherosclerosis; ApoE/LDLR-/- mice

Transcatheter aortic valve implantation and minimally invasive treatment of aortic valve stenosis - long-term results, complications, prognostic factors and assessment of the quality of life - Tokarek, Tomasz (2018)
The PhD dissertation presented an assessment of the long-term clinical outcomes and quality of life (QoL) in patients with severe aortic stenosis treated with transcatheter aortic valve implantation (TAVI) and available cardiac surgery methods (sternotomy, minithoracotomy, ministernotomy). There was no difference between groups in terms of the longest available follow-up mortality. TAVI seems to have a more favorable effect on left ventricular function and an increase in ejection fraction in comparison with the surgical methods. However, arrhythmias and conduction disturbances after the procedure were more often reported in TAVI patients. Amelioration of QoL after TAVI in comparison with surgical treatment groups was maintained up to one year after the procedure. In multivariable Cox regression analysis incomplete coronary revascularisation, estimated glomerular filtration rate, previous stroke/tran¬sient ischaemic attack and blood transfusion were identified as the only independent determinants of death in TAVI patients. Different tools for frailty evaluation were presented. Sarcopenia was evaluated with psoas muscle area and volume using computed tomography scans. Results were normalized for body surface area. This method had the highest discrimination ability among all the tested frailty tools for 12-month all-cause mortality after TAVI. The PhD dissertation confirmedutility of the frailty and QoL evaluation in patients undergoing TAVI.Transcatheter aortic valve implantation and minimally invasive treatment of aortic valve stenosis - long-term results, complications, prognostic factors and assessment of the quality of life
Keywords: aortic valve stenosis; TAVI; quality of life; frailty; surgical aortic valve replacement

Patient with problems in social functioning in long term care facility - Horwath, Urszula (2018)
Introduction The main goal of this doctoral dissertation is to analyze the risk factors of behavioral symptoms and unsettled relationships among residents and between residents and staff, as well as risk factors related to the frustration experienced by staff in contact with resident in long-term care facility (LTCF). Moreover this study aims to analyze the line of pharmacological treatment (including antipsychotics, antidepressants, sedatives drugs) and non-pharmacological treatment (categorized as physiotherapy, occupational therapy, psychological care and ADL training) administered to the LTCF residents who manifest behavioral symptoms and unsettled relationships.So far, the behavioral symptoms, as well as unsettled relationships have not been analyzed among polish LTCF residents. Many polish research studies analyze the behavioral disturbances in the context of neuropsychiatric symptoms accompanying dementia. This paper is focused on the analysis of behavioral symptoms and unsettled relationships in the typical LTCF population which consists of residents with variety of chronic somatic and mental diseases, not only limited to patients with dementia. Goals of the study:1) The analysis of risk factors of behavioral symptoms such as verbal and physical aggression, inappropriate social behavior, wandering and resistance to prescribed care and treatment in the LTCF population.2) The analysis of risk factors of unsettled relationships among residents and between residents and staff, as well as determinants related to the frustration experienced by staff in contact with resident.3) The analysis of the treatment approach of LTCF residents with behavioral symptoms and/or unsettled relationships in terms of pharmacological and non-pharmacological interventions. Research hypotheses:1) The behavioral symptoms and unsettled relationships are frequent among LTCF residents.2) Symptoms of depression constitute a significant risk factor of behavioral symptoms, unsettled relationshipsand/or frustration experienced by staff in contact with resident in LTCF.3) Cognitive impairment is an independent risk factor of the occurrence of behavioral symptoms and unsettled relationships among LTCF residents.4) Some somatic diseases in LTCF residents increase the risk of unsettled relationships and/or frustration experienced by staff in contact with resident.5) The LTCF residents manifesting behavioral symptoms and/or unsettled relationships are predominantly treated symptomatically, using antipsychotic and sedative drugs.
Keywords: long -term care facility (LTCF); behavioral symptoms; unsettled relationships between residents; unsettled relationships between resident and staff; depression

Evaluation of activity of selected chalcogen-containing compounds against bacterial multidrug-resistance - Witek, Karolina (2018)
Keywords: bacterial multidrug-resistance; ESKAPE pathogens; chalcogen-based compounds; antibacterial agents; antibiotic adjuvants

The role of the family in the treatment of chronic non-terminal cardiometabolic diseases in the elderly – the perspective of family medicine - Jarczewska, Dorota Łucja (2017)
INTRODUCTION: The compliance with medical recommendations can be supported by informal family caregivers who live with elderly patients suffering from cardiometabolic diseases. AIM: To analyze different types of care for elderly people among their family caregivers and to identify potential and actual intervention made by a family doctor in order to ensure better care provided by the caregivers. METHODS: A qualitative study design adopting a grounded theory approach was used. Unstructured, in-depth, qualitative interviews were conducted among 17 patients and their first informal caregivers living in Krakow. Theoretical sample included 3 family doctors. Interviews were audio recorded, transcribed verbatim and analyzed. RESULTS, CONCULUSIONS: The theory of role acceptance was composed of four dimensions: cognitive, emotional, communicative and in household duties. Five strategies of acceptance of the patient’s role and one strategy due to denial were identified. A caregiver’s attitude according to the patients’ needs included filling needs, creating needs, removal of the needs and needs deprivation. Some potential social interventions made by a family doctor were defined. These data enable family doctors to undertake adequate pattern of behavior towards different types of patients and efficiently use social interventions to make better communication within the patient’s family.
Keywords: family caregiver; family doctor; cardiometabolic diseases; cardiovascular diseases